Study of Asymmetries in 0.4 kV Distribution Line with Different Schemes of Supply Transformers and Connection of Single-phase Renewable Energy Source - Bosneaga, Valeriu; Suslov, Victor (Problems of the regional energetics, 2025)
The aim of the work is studying asymmetric modes of 10/0.4 kV distribution transformers at connecting single-phase renewable energy sources. This problem is relevant due to increasingly use of such sources. To achieve this goal, calculation of asymmetric modes, asymmetry coefficients for zero and negative sequences and values of phase voltages is performed. This proposed model is novel since it allows analyzing the asymmetry coefficients when connecting single-phase sources directly to distribution transformer low-voltage buses or via supplying three-phase line. Important is that transformer connection diagram is taken into account. It is shown that D/y0 connection has significant advantages over Y/y0 diagram, which is impractical in these modes. When injecting directly onto transformer low-voltage buses, the D/y0 circuit ensures permissible values of phase voltages and asymmetry coefficients in the entire range of injection variation, up to rated current of the transformer. Permissible values of injection via the three-phase line are significantly reduced due to the noticeable negative effect of its zero-sequence impedance. For estimation of injection permissible value depending on three-phase line length and its parameters, it is necessary to calculate the mode. Y/z0 circuit has somewhat better indicators compared to D/y0 circuit. In the case of connecting a single-phase generation source through a three-phase 4-core cable, the permissible value of injection is limited not so much by transformer parameters as mainly by the significantly higher zero-sequence impedance of the cable.